Traditional Ceramics in Jordan : Issues, Challenges and Ceramic-Design Collaboration for Sustainability - Saleem, Mohammad Ali Ayesh (2019)
The purpose of this research is to heighten the level of sustainability of traditional ceramics studios in Jordan by broadening the usage of traditional handcrafted ceramics focus in home accessories and a complementary element for interior design. It explores the opportunities and addresses the status of traditional ceramics enterprises in Jordan. The research focuses on associated issues and challenges facing this industry. In addition, it establishes an organized and systematic approach for innovation and developing new ceramic products by collaboration between ceramics artisans and designers. This research mainly uses the qualitative research approach, which includes several methods such as primary interviews, historical enquiry and observation. In addition, practice-based research is employed when executing phase three, which deals with producing and developing new ceramic products. These new products are developed through a collaboration process between ceramics artisans and designers. It is hoped that the installation of such artworks will give sustainability to the local ceramics enterprises by increasing the demand of ceramics. This research provides a description of the ceramics business context as well as the challenges and issues related to the field. This research is significant for several different contributions. Firstly, from an academic perspective, this topic is comparatively new in Jordan; as only limited research has been conducted on the ceramics handcraft sector and its issues. In addition, the research for sustainability of micro and small ceramics enterprises is still in its infancy stage in Jordan. However, there are gaps in the literature relating to handcraft enterprises, particularly in ceramics. Furthermore, applying the findings and theories of other international research contexts to that of Jordan may not always be probable. The research has identified and addressed the challenges and issues faced by the traditional ceramics enterprises. It also reveals the importance of the new media such as the internet and social media as a free or low-cost platform for marketing. The findings of this qualitative research will result in original knowledge of Jordanian ceramics enterprises and the development of the sector.